Making Meaning of the Pandemic Through Symbols in Literary Work - Rahmawati, Irma; Budi, Wahyu (KnE Social Sciences, 2023)
The COVID-19 pandemic is still a thing people think about and deal with. It affects everything, including literature. Arguably, making meaning of a pandemic through literature can be a helpful strategy to cope with the situation. This paper aims to observe the meaning of the symbols in a novel by Herman Melville, Moby Dick. The story possesses various symbolic meanings and can relate to the metaphorical point of view of the pandemic. The paper uses a qualitative methodology to focus on finding the symbols, the themes represented, and the meaning of the symbols for each character and relating them to post-pandemic situations using a qualitative methodology. The theory of symbolism by Susanne Langer is employed to identify and analyze the symbols in Moby Dick. This paper results on the symbols’ relevance and creates meaning for the situation of the post Covid-19 pandemic. Keywords: post pandemic, literature, novel, symbolism